Penerapan ISAK Nomor 35 tentang penyajian laporan keuangan entitas berorientasi nonlaba pada Yayasan Sekolah Luar Biasa Finjil Bitung - Makawekes, Marsella Thavitia; Alexander, Stanly W.; Tirayoh, Victorina Z. (Manajemen Bisnis dan Keuangan Korporat, 2025)
Accountable and transparent financial reporting is essential for non-profit-oriented entities, including educational foundations, as a form of responsibility to stakeholders in the use of public funds. The Interpretation of Financial Accounting Standards (ISAK) Number 35, issued by the Indonesian Institute of Accountants (IAI), provides specific guidelines for preparing financial statements of non-profit entities. However, in practice, many foundations have not fully understood or implemented this standard consistently. This study aims to evaluate the implementation of ISAK Number 35 at the Finjil Bitung Special Needs School Foundation. A descriptive qualitative method was employed, utilizing in-depth interviews, direct observation, and documentation of the foundation’s financial reports. Data were analyzed by comparing the foundation’s financial reporting practices with the requirements set forth in ISAK Number 35. The results reveal that the financial statements have not been prepared in accordance with ISAK 35, particularly regarding the classification of restricted and unrestricted funds, and the lack of separation between non-profit and operational activities. These findings indicate a limited understanding of applicable accounting standards among the foundation's financial managers. Theoretically, this study contributes to the literature on ISAK 35 implementation in educational non-profit entities. Practically, it highlights the need for improved human resource capacity and encourages the preparation of financial reports that are more accountable and in line with applicable standards